The association between social environment factors and physical activity engagement among Chinese adolescents - Yuan Yuan; Sauwakon Ratanawijitrasin; Changle Li; Francois Rene Lamy (Discover Social Science and Health)
Abstract Background The high proportion of physically inactive Chinese adolescents highlights the need to address the social determinants of physical activity within this particular group. Studies regarding the associated social environment factors of physical activity among adolescents remain limited. This study aimed to explore the association between social environmental factors and physical activity in adolescents, with a particular focus on the role of social capital in family and school settings. Method Descriptive statistics and generalized ordered logistic regression analyses utilizing cross-sectional data from the 2015 China Educational Panel Survey were employed. Results The results indicated that 93.5% of the adolescents involved in the study failed to meet the recommended daily physical activity of one hour. Family social capital indicators, including adolescent–parent communication, parental involvement, and household rules, were positively associated with higher levels of physical activity among adolescents. Additionally, school social capital indicators, including adolescents' perceived closeness with peers and their interaction with peers, showed a positive association with higher levels of physical activity among adolescents. Conclusion The findings that social capital indicators were positively associated with physical activity among adolescents suggest that intervention programs should focus on creating a supportive environment to enhance these social capitals for adolescents, thereby promoting their physical activity engagement.